After war the political economy of exporting democracy - Coyne, Christopher J. (Stanford University Press, 2018)
The United States has attempted to generate change in foreign countries by exporting liberal democratic institutions through military occupation and reconstruction. Coyne examines mechanisms and institutions that contribute to success of reconstruction programs by creating incentives for sustained cooperation. He offers two alternatives to reconstruction programs that could serve as catalysts for social change: principled non-intervention and unilateral free trade.